"Breathing" unimolecular micelles based on a novel star-like amphiphilic hybrid copolymer1. Issue 23 (21st June 2015) - Fan, Xiaoshan; Wang, Zhuo; He, Chaobin
<x xml:space="preserve">Abstract</x> Novel unimolecular micelles that possess a pH-induced "breathing" feature are presented in this paper.